PROKRASTINASI AKADEMIK MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING IKIP PGRI MADIUN DITINJAU DARI EFIKASI DIRI, FEAR OF FAILURE, GAYA PENGASUHAN ORANG TUA, DAN IKLIM AKADEMIK - Dahlia Novarianing Asri; Noviyanti Kartika Dewi (IKIP PGRI MADIUN, 2014)
Numerous studies have reported that several factors negatively and positively affect academic procrastination among college students, such as time management, motivation, self-efficacy, coping styles, self-worth, self esteem, and etc. The studies reported that self-efficacy, fear of failure, parent style, and academic climate are related with academic procrastination. Students with high level of procrastination reported that they have low level of self-efficacy, fear of failure, parent style, and academic climate. The purpose of this study is to find out the correlation between self-efficacy, fear of failure, parent style, and academic climate on academic procrastination. The participants were 90 students who study at the Guidance and Counselling, Faculty of Education in IKIP PGRI Madiun. Each participant completed five scales: the self-efficacy scales, the fear of failure scales, the parent style, the academic climate, and the academic procrastination. This result of this research suggests that in general, there is a very significant correlation between self-efficacy, fear of failure, parent style, and academic climate. Effective total contribution of self-efficacy, fear of failure, parent style, and academic climate to academic procrastination are 0.193%,and the greatestcontribution is from academic climate, 0.058%.